TO FAMILY KRESTOTSVETNYE CHARACTERISTIC, OR CABBAGE (CRUCIFERAE, BRASSICACEAE) IN FLORA CHR - R. S. ERZHAPOVA; Z. I. IRISHANOVA; Z. N. AMALOVA; Ya. E. LORSANOVA (Юг России: экология, развитие)
This article shows list of systemic cabbage kinds among CHR flora, theirs geographical spreading.